Analysis of the relationship between the working environment and employee performance in selected construction firms in Karachi city - Muhammad Tarique Lakhiara Lakhiara; Abd Halid Abdullah; Muhammad Tahir Lakhiar (Neutron, 2021)
A healthy working environment is important for the performance of workers to prevent undue burden on employees, thus impacting their job efficiency. Numerous working environment factors contributed to job satisfaction. The goal of this analysis was, therefore, to explore the correlation between working environment and the employee performance on the basis of five working environment dimensions. This study utilized the quantitative approach and collected data through questionnaires. The respondents of this study were employees of all positions, which include the manager, senior to junior executives in selected construction firms of Karachi city. By using Pearson's Correlation Analysis, the data were analyzed to measure the relationship among variables. The results indicate that the workplace environment and employee performance have a significant relationship. The support of supervisors was thus identified as the main element in maintaining a positive workplace environment.